Community Inclusion in PrEP Demonstration Projects: Lessons for Scaling Up. - Reza-Paul, Sushena; Lazarus, Lisa; Jana, Smarajit; Ray, Protim; Mugo, Nelly; Ngure, Kenneth; Folayan, Morenike Oluwatoyin; Durueke, Florita; Idoko, John; Béhanzin, Luc; Alary, Michel; Gueye, Daouda; et al. (plos one, 2023)
26p